The IL-4 Level among Patients with Autoimmune Thyroiditis in Al-Najaf Governorate, Iraq - Sarah Hasan Kadhum Al-Huchaimi; Mahdi Hussain Alammar; Sabah N. Al-Fatlawi (Medical Journal of Babylon, 2025)
Background: The study of autoimmune thyroiditis is considered one of the challenges of sustainable development. Autoimmune thyroiditis includes largely cellular and humoral immune responses targeted at the thyroid gland, including Graves thyroiditis and Hashimoto’s thyroiditis. Objectives: This study aimed to find out the relationship between autoimmune thyroiditis and interleukin-4 (IL-4) levels in infected patients and compare them with healthy individuals by using the enzyme-linked immunosorbent assay (ELISA) technique. Materials and Methods: Sixty-two samples were collected from patients with autoimmune thyroiditis in AL-Najaf Governorate and 30 samples from healthy individuals as a control group during the period from March to September 2022. Blood was collected in a gel tube to isolate the serum and measure the IL-4 level using the ELISA technique. Results: This study included 46/62 women and 14/62 men with autoimmune thyroiditis, aged between 20 and 65 years. The results showed that the 50 to 59 age group was the most affected. Autoimmune thyroiditis (Graves or Hashimoto’s) had a significant effect P < 0.01 on the level of IL-4. The type of injury had a significant effect on the level of IL-4, as our results showed that people with Graves disease were more affected by the disease compared to those with Hashimoto’s disease, through compared with the control group. Conclusion: There is a high level of IL-4 in patients with autoimmune thyroiditis, which means that IL-4 has an important role in the development of the disease in patients with autoimmune thyroiditis when compared to healthy individuals.